THE MAIN STRUCTURAL-PALEOGEODYNAMIC TYPES OF UKRAINIAN SHIELD GRANITOIDS AND THEIR PETROPHYSICAL CHARACTERISTICS - Tolstoy, M.; Shabatura, O.; Kostenko, N.; Gasanov, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the basis of petrogenetic reconstructions the paleogeodinamics classification of granitoid complexes of the Ukrainian Shield is executed. The evolution of geodynamics conditions of formation of the rocks and their physical properties are shown.